2021
DOI: 10.1002/chem.202100512
|View full text |Cite
|
Sign up to set email alerts
|

A Luminescent Two‐Coordinate AuIBimetallic Complex with a Tandem‐Carbene Structure: A Molecular Design for the Enhancement of TADF Radiative Decay Rate

Abstract: A luminescent bimetallic AuI complex comprised of N‐heterocyclic carbene (NHC) and carbazole (Cz) ligands, that is, (NHC’)Au(NHC)AuCz has been synthesized and studied. Both carbene ligands in the bimetallic complex act as electron acceptors in tandem to increase the energy separation between the ground and excited state, which is higher than those found in either monometallic analogue, (NHC)AuCz and (NHC’)AuCz. A coplanar geometry designed into the tandem complex ensures sufficient electronic coupling between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 73 publications
(64 reference statements)
0
24
0
Order By: Relevance
“…As revealed by the diffraction results, the molecules present linear two-coordination geometry with near coplanar orientation of NHC and carbazole ligands in agreement with data from analogous cMa derivatives. [29][30][31]48 The dihedral angles between the two ligands planes range from 0.31 to 12.71. The C NHC -M bond is longer than the M-N Cz bond in Me-Cu, but they become near equal in Me-Ag.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As revealed by the diffraction results, the molecules present linear two-coordination geometry with near coplanar orientation of NHC and carbazole ligands in agreement with data from analogous cMa derivatives. [29][30][31]48 The dihedral angles between the two ligands planes range from 0.31 to 12.71. The C NHC -M bond is longer than the M-N Cz bond in Me-Cu, but they become near equal in Me-Ag.…”
Section: Resultsmentioning
confidence: 99%
“…25,[28][29][30]37 Investigations have been carried out focusing on two-coordinate TADF complexes experimentally and theoretically, to develop structure-property relationships and strategies to achieve high radiative (k r ) and low non-radiative (k nr ) decay rates. [29][30][31]38,[43][44][45][46][47][48] TADF molecules fall into two basic categories, depending on whether they have slow or fast rates for intersystem crossing (ISC). 12 Organic TADF materials generally have slow ISC rates (k ISC = 10 5 -10 8 s À1 ) owing to weak spin-orbital coupling (SOC), which makes fluorescent radiative decay k S 1 r À Á competitive with intersystem crossing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Thompson and co-workers have demonstrated that digold complexes comprised of d-NHCs D and carbazole ligands exhibited an enhanced luminescence efficiency. The d-NHCs could act as electron acceptors to increase the energy separation between the ground and excited states, which is higher than that observed in the monometallic analogue …”
mentioning
confidence: 79%
“…16,17 Due to a favorable electronic level configuration and metal involvement TADF lifetimes below 1.0 μs can be achieved. 18,19 Here we present a novel approach towards TADF emitters that can be considered as a hybrid case between the previously discussed all-organic through-space and metal-assisted designs (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%